Effect of high versus low initial doses of L-thyroxine for congenital hypothyroidism on thyroid function and somatic growth. Issue 11 (2nd May 2008) - Jones, J H; Gellén, B; Paterson, W F; Beaton, S; Donaldson, M D C
Abstract : Background and aims: The optimal dose of thyroxine (T4) in congenital hypothyroidism (CH) during infancy is controversial. Higher doses lead to improvement in cognitive scores, but have been linked to later behavioural difficulties. We have examined the effects of initial T4 dosage on somatic growth — a putative surrogate marker of overtreatment. Methods: 314 CH children (214 girls, 100 boys) were analysed according to initial daily dose of T4: Group 1 (25 μg, n = 152), Group 2 (30–40 μg, n = 63) and Group 3 (50 μg, n = 99). Thyroid function and weight, length and occipito-frontal head circumference (OFC) standard deviation score (SDS) were compared at 3, 6, 12, 18, 24 and 36 months of age. Linear growth SDS was compared between the three groups using a regression adjustment model at 12 and 18 months of age using birth weight and 3-month data as baselines. Thyroid function was also compared at diagnosis (T0 ), and 7–21 days after the start of treatment (T1 ). Results: At T1 median thyroid stimulating hormone (TSH) for Groups 1, 2 and 3 was 58, 29 and 4.1 mU/l, respectively (p<0.001), Group 3 values remaining significantly lower at 3 and 6 months. Median free T4 (fT4) was within or just above the reference range in all groups at T1, but 7.4% of Group 1 had values <9 pmol/l compared with 5.1% and 0% for Groups 2 and 3, respectively. At 3 months weight, length and OFC SDS values were −0.39, −0.35, 0.09; −0.30, −0.47, 0.32; and −0.03, −0.13, 0.18 for Groups 1, 2 and 3, respectively, indicating relatively large OFC in all infants. A regression adjustment model showed no significant difference in growth rate from baseline and 12 or 18 months of age, between the three groups. Conclusion: An initial T4 dose of 50 μg daily, normalises thyroid function several months earlier than lower-dose regimes, with no evidence of sustained somatic overgrowth between 3 months and 3 years.